HIGH-SPIN STATES IN K(PI)=1/2(-) BAND OF F-19 - Underwoo, B; Wormald, M; Anyaswei, N; Jelley, N; Allen, K (1974)
Resonances in the 15N(α, γ)19F reaction at Eα = 5413 ± 5 keV and 6258 ± 5 keV corresponding to levels in 19F at Ex = 8288 ± 2 keV and 8957 ± 2 keV have been studied. Angular distribution and ωγ measurements indicate that the level at 8288 keV has Jπ = 13 2-( 9 2-),while that at 8957 keV has Jπ = 11 2+. The values of ωγ are 0.53 ± 0.08 eV and 0.9 ± 0.17 eV respectively. The 8288 keV level decays by a 22.4 ± 3.3 W.u. E2 transition to the 9 2- state at 4032 keV and is suggested to be the 13 2- member of the Kπ = 1 2- band. © 1974.